The Value of Emotional Intelligence: Self-Awareness, Self-Regulation, Motivation, and Empathy as Key Components - Antonopoulou, Hera (Technium Education and Humanities, 2024)
This paper aims to review the concept of Emotional Intelligence systematically. In essence, Emotional Intelligence pertains to our capacity to identify, comprehend, and regulate our own emotions, as well as the emotions of others, thereby fostering the cultivation of positive interpersonal connections. This study will examine the dimensions of Emotional Intelligence outlined by researchers, exploring its definitions, associations with age and gender, assessment methods, and overall advantages. Consequently, a comprehensive and methodical review of the existing literature was conducted using prominent academic databases such as Science Direct, Google Scholar, ResearchGate, and APA PsycNet. In summary, Emotional Intelligence is not a singular, homogeneous concept but a combination of various interconnected components. Integrating self-awareness, self-regulation, motivation, and empathy enables individuals to navigate their social environment effectively, rendering emotional intelligence (EI) a precious asset in both personal and professional domains.